Variation of the diet of artibeus lituratus and sturnira lilium (Chiroptera: Phyllostomidae) in three phytogeographic regions of southern Brazil - Bôlla, Daniela A. S.; Carvalho, Fernando; Gazarini, Janaina; Zocche, Jairo J.; Pedro, Wagner A. [UNESP] (My University, 2018)
The family Phyllostomidae has the greatest morphological and ecological diversity among Neotropical bats, playing important roles in forest environments. This study aimed to compare the diet of Artibeus lituratus and Sturnira lilium in three phytophysiognomies in the Atlantic Forest biome in Southern Brazil-Ombrophilous Dense Forest (FOD), Semideciduous Seasonal Forest (FES) and Restinga (FPIM). Bats were sampled monthly along a year using mist nets. Bat’s diet was analyzed in feces following a standardized protocol. We analyzed data on diet composition by richness, abundance and similarity among the three sampled regions (Non-metric Multidimensional Scaling and Bray-Curtis Index). Samples from FES were the most abundant for both A. lituratus and S. lilium, with Ficus and Cecropia being the most consumed genera for the first species and Solanum for the second one in all sampled sites. The abundance of feeding items varied across phytogeographic regions.
Variação na dieta de artibeus lituratus e sturnira lilium (Chiroptera: phyllostomidae) em três regiões fitogeográficas no sul do Brasil
Keywords: Atlantic Forest; Bats; Feeding plasticity; Frugivory